If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 2) = 115 Reorder the terms: 5(2 + 3x) = 115 (2 * 5 + 3x * 5) = 115 (10 + 15x) = 115 Solving 10 + 15x = 115 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 15x = 115 + -10 Combine like terms: 10 + -10 = 0 0 + 15x = 115 + -10 15x = 115 + -10 Combine like terms: 115 + -10 = 105 15x = 105 Divide each side by '15'. x = 7 Simplifying x = 7
| 1/7(x+21)=6 | | -7x+10=-3x-22 | | x^3-16x^2+20x+400=0 | | 3x(x)+8x=5x-4x(x) | | 2x+2=-22+5x | | (3w-1/2)=(6w-2/7)+3 | | -56-7x=19+8x | | z=14x+5y | | 7x-4=x+56 | | (11.2)2-(0.375/3) | | ((6t)^2+9)^1/2 | | 5x(x)=10x | | (.0105)(.1417)= | | -243=-90(10+x) | | p=m(1-DT) | | 120=-12(x-5) | | 7(4-x)+9=1+4(x-1) | | x-1+x=-9 | | 2x+6x+8=6x+4 | | 5x-6+3x=-6 | | 5-t-3=-1+2(t-3) | | 4x+7=-8x-29 | | 4g-4=40 | | 4+x+7x=76 | | 6-5x=-44 | | 15x(x)-15x=0 | | 1+1-2-x=-4(x+2) | | -9+7x=-65 | | 143-5x=11+6x | | 35+10x=3x | | 15z^3-4z^2=35z | | 11x-97=-9 |